Volumen Plaquetario Medio como Predictor de Preeclampsia con Características de Severidad en un Hospital de Trujillo - Zavaleta Reyes, Christians Josset (2021)
Preeclampsia is a disease that maintains a constant prevalence and incidence in our environment; For this reason, it is important to identify those factors related to its prognosis; on the other hand, alterations in platelet indices, including mean platelet volume, constitute hematological alterations that have been recognized with greater frequency. Objective: To determine if the mean platelet volume is a predictor for preeclampsia with characteristics of severity. Method: The present work of investigation is of diagnostic tests, analytical. Observational, retrospective. Conclusions: The mean platelet volume is a predictor of Preeclampsia with characteristics of severity in a hospital in Trujillo.